Stakeholder perspectives on injury prevention training in girls' and women's elite football: A group concept mapping study involving coaches, physical performance coaches, physical therapists, medical doctors, and club management - Bandak, E.; Thorborg, K.; Alkjær, T.; Zebis, M. K.; Wæhrens, E. E. (Physical Therapy in Sport, 2025)
Objectives To identify factors influencing use of injury prevention training among stakeholders of Danish girls' and women's elite football teams.